Long‐term ecological research and the COVID‐19 anthropause: A window to understanding social–ecological disturbance. Issue 4 (8th April 2022) - Gaiser, Evelyn E.; Kominoski, John S.; McKnight, Diane M.; Bahlai, Christie A.; Cheng, Chingwen; Record, Sydne; Wollheim, Wilfred M.; Christianson, Kyle R.; Downs, Martha R.; Hawman, Peter A.; Holbrook, Sally J.; Kumar, Abhishek; et al.
Abstract: The period of disrupted human activity caused by the COVID‐19 pandemic, coined the "anthropause, " altered the nature of interactions between humans and ecosystems. It is uncertain how the anthropause has changed ecosystem states, functions, and feedback to human systems through shifts in ecosystem services. Here, we used an existing disturbance framework to propose new investigation pathways for coordinated studies of distributed, long‐term social‐ecological research to capture effects of the anthropause. Although it is still too early to comprehensively evaluate effects due to pandemic‐related delays in data availability and ecological response lags, we detail three case studies that show how long‐term data can be used to document and interpret changes in air and water quality and wildlife populations and behavior coinciding with the anthropause. These early findings may guide interpretations of effects of the anthropause as it interacts with other ongoing environmental changes in the future, particularly highlighting the importance of long‐term data in separating disturbance impacts from natural variation and long‐term trends. Effects of this global disturbance have local to global effects on ecosystems with feedback to social systems that may be detectable at spatial scales captured by nationally to globally distributed research networks.